Distributed Leadership in Irish Post-Primary Schools: Policy versus Practitioner Interpretations - Niamh Hickey; Aishling Flaherty; Patricia Mannix McNamara (MDPI AG, 2023)
School leaders have faced significant challenges since the beginning of the COVID-19 pandemic. Distributed leadership has become the default leadership response implemented by schools to manage increased pressure. While Irish schools have traditionally operated behind a 'closed-door', there has recently been a movement towards a shared model of leadership, and Irish school leadership policy currently endorses the adoption of a distributed leadership model. Increased interest and policy endorsement notwithstanding, distributed leadership remains an elusive concept. The aim of this study was to explore Irish post-primary school personnel's interpretations of distributed leadership and analyse these interpretations through a teacher empowerment lens with respect to Irish school leadership policy. This study reports the results of a thematic analysis of 363 survey responses provided by post-primary school personnel. Short's six dimensions of teacher empowerment were utilised to inform a framework for thematically analysing the participants' interpretations. An initial framework for enacting distributed leadership through an empowerment lens was outlined. Interpretations were found to diverge regarding (i) what is shared, (ii) who it is shared with, and (iii) how it is shared. This paper adds to the corpus of knowledge concerning how distributed leadership is understood in practice and will aid in informing future school leadership policy documents.